Morphological and primary structural consistency of fibrils from different AA patients (common variant). (3rd July 2019) - Liberta, Falk; Rennegarbe, Matthies; Rösler, Reinhild; Bijzet, Johan; Wiese, Sebastian; Hazenberg, Bouke P.C.; Fändrich, Marcus
Abstract: Aims: To test the hypothesis that the fibril morphology and the fibril protein primary structure are conserved across different patients suffering from the common variant of systemic Amyloid A( AA) amyloidosis. Methods: Amyloid fibrils were extracted from the renal tissue of four patients. The fibril morphology was analysed in negatively stained samples with transmission electron microscopy (TEM). The fibril protein identity and fragment length were determined by using mass spectrometry. Results: The fibrils show a consistent morphology in all four patients and exhibit an average width of ∼9.6 nm and an average pitch of ∼112 nm. All fibrils are composed of polypeptide chains that can be assigned to human serum amyloid A (SAA) 1.1 protein. All fragments lack the N-terminal arginine residue and are C-terminally truncated. Differences exist concerning the exact C-terminal cleavage site. The most prominent cleavage site occurs at residues 64–67. Conclusions: Our data demonstrate that AA amyloid fibrils are consistent at the level of the protein primary structure and fibril morphology in the four analysed patients.